(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
The failure of the re-annexation of the Dominican Republic to Spain between 1861 and 1865 conditioned the relations between both countries over the next decade. Spanish-Dominican relations were not only mediated by the increased risk of annexation of the Caribbean republic to the United States, especially during the administrations of Cabral and Baez, but also by the outbreak of the Cuban crisis in 1868. This complex scenario forced the Spanish diplomacy to attempt a rapprochement with its former colony. The normalization of relations between the two countries would be, however, hampered by internal Dominican instability and because of the sympathy the Cuban insurgents found among important sectors of society and the Dominican political class. This paper analyzes this process and explores the reasons that postponed the resumption of diplomatic relations between Dominicans and Spaniards until the late 1870’s.